Field measurement of atmospheric CO₂ column abundance based on portable laser heterodyne radiometer - Wang, Yong; Zhang, Maolei; Wang, Jiapeng; Wang, Gang; Cui, Ruyue; Dong, Lei; Wu, Hongpeng (Frontiers in Physics, 2025)
This study presents a portable near-infrared laser heterodyne radiometer specifically designed for measuring the column abundance of atmospheric carbon dioxide (CO₂) in the Taiyuan area. The instrument modulates the solar radiation using a fiber optic switch and amplifies the solar radiation through a semiconductor optical amplifier. The local oscillator laser is progressively scanned at the strong absorption characteristic of 1572.02 nm. Two beams of light are mixed on the photodetector to produce a heterodyne signal. To enhance performance, the radio frequency (RF) circuit system of the radiometer was thoroughly optimized, including adjustments to the filter bandwidth and the integration time of the lock-in amplifier. These improvements significantly enhanced the spectral signal-to-noise ratio (SNR) to a high level of 130 and achieved a spectral resolution of 0.0083 cm⁻1. The laser heterodyne signals were demodulated using a lock-in amplifier. Furthermore, a forward model based on line-by-line integration and an iterative fitting algorithm were employed to achieve high-precision CO₂ column abundance calculations. Outdoor field measurements conducted at Shanxi University validated the feasibility and practicality of this approach, laying a solid foundation for its broader application.